建立行政立法成本效益分析制度 ：问题和挑战 = Establishment of a cost and benefit evaluation framework for administrative legislations: issues and challenges - 李冰 Li, Bing (2010)
2004年国务院《全面推进依法行政实施纲要》中要求：积极探索对政府立法项目尤其是经济立法项目的成本效益分析制度。然六年过去了，尽管从国家到少数地方政府做了一些努力和尝试，应当说这项工作的前景还很不明朗。针对这一现状，本文试图从一个行政立法工作者的角度，去探究在建立这项制度中存在的主要问题，并力求提出具有针对性的解决问题的思路和建议。 2004 the State Council, "Implementation Outline for comprehensively promoting administration according to law"in the request: actively explore the government's legislative projects, especially economic legislation system of the project cost-benefit analysis. However, six years later, despite the small number of local government from national to make some effort and try, it should be said that the prospect of this work is far from clear. For this situation, this paper attempts from a perspective of the executive and legislative workers, to explore the system in the establishment of the main problems and to seek forward-focused ideas and suggestions to solve the problem.